2008
DOI: 10.1002/app.28774
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of new monomeric and polymeric phthalocyanines

Abstract: Monomeric (M ¼ 2Li or 2H) and polymeric (M ¼ 2H, Zn, Cu, Co, or Ni), where M is metal or hydrogen, phthalocyanines were prepared by the tetramerization reaction of bisphthalonitrile monomer with appropriate materials. The electrical conductivities of the polymeric phthalocyanines, which were measured as gold sandwiches, were found to be 10 À10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…1b) and the signals at 0.83-1.52 ppm derived from myristyl group-H were present in the 1 H NMR spectrum of compound 3 (Fig. 2a) (Bilgin et al 2008) was found in the FTIR spectrum of compound 4 (Fig. 1c).…”
Section: Resultsmentioning
confidence: 88%
“…1b) and the signals at 0.83-1.52 ppm derived from myristyl group-H were present in the 1 H NMR spectrum of compound 3 (Fig. 2a) (Bilgin et al 2008) was found in the FTIR spectrum of compound 4 (Fig. 1c).…”
Section: Resultsmentioning
confidence: 88%
“…20,28,30 The polymeric metal-free phthalocyanine with imido end groups was dried under vacuum after the appropriate purification steps. …”
Section: The Conversion Of Cyano End Groups Of the Polymeric Metal-frmentioning
confidence: 99%
“…The conversion of cyano end groups of the polymeric metal-free phthalocyanine into imido groups was performed according to the literature with small changes in the purification part. 20,28,30 The polymeric metal-free phthalocyanine with imido end groups was dried under vacuum after the appropriate purification steps.…”
Section: The Conversion Of Cyano End Groups Of the Polymeric Metal-free Phthalocyanine Into Imido Groups (4a)mentioning
confidence: 99%
“…Bilgin et al (2008) reported the analysis of monomeric and polymeric phthalocyanines of metals like Zn, Cu, Co, and Ni using mass spectrometry, nuclear magnetic resonance NMR imaging, and thermogravimetry. Wyatt et al (2006) have reported the characterization of various porphyrins and phthalocyanines using matrixassisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%